2020
DOI: 10.1016/j.jaci.2020.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of severity and threshold of allergic reactions during oral peanut challenges

Abstract: Background Oral food challenge (OFC) is the criterion standard to assess peanut allergy (PA), but it involves a risk of allergic reactions of unpredictable severity. Objective Our aim was to identify biomarkers for risk of severe reactions or low dose threshold during OFC to peanut. Methods We assessed Learning Early about Peanut Allergy study, Persistance of Oral Tolerance to Peanut study, and Peanut Allergy Sensitization study participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 38 publications
12
127
1
2
Order By: Relevance
“…Two recent studies of peanut allergy found a relationship of reactivity and symptom severity 25,33 ; however, in a study of wasp venom allergy, basophil reactivity to wasp allergen extract could not predict patients symptom severity 34 . The latter study set the scene for developing methods to assess basophil sensitivity 35 , that has been shown to be useful in the diagnosis of allergic asthma 36 , rhinitis 37 , food allergy 33,[38][39][40] , allergen immunotherapy [41][42][43][44][45] and anti-IgE therapy 46-48 . Basophil sensitivity refers to the allergen concentration eliciting half-maximal basophil activation and can be expressed as EC 50 that decreases with increasing severity 42,45 , or CD-sens which is the inverse of EC 50 multiplied by 100 and can be calculated based on the slope of the dose-response curve 25,35 . CD-sens increases with the severity of allergic reactions 35 .…”
Section: Reactivity and Sensitivity Are Distinct Measures Of Basophilmentioning
confidence: 90%
See 2 more Smart Citations
“…Two recent studies of peanut allergy found a relationship of reactivity and symptom severity 25,33 ; however, in a study of wasp venom allergy, basophil reactivity to wasp allergen extract could not predict patients symptom severity 34 . The latter study set the scene for developing methods to assess basophil sensitivity 35 , that has been shown to be useful in the diagnosis of allergic asthma 36 , rhinitis 37 , food allergy 33,[38][39][40] , allergen immunotherapy [41][42][43][44][45] and anti-IgE therapy 46-48 . Basophil sensitivity refers to the allergen concentration eliciting half-maximal basophil activation and can be expressed as EC 50 that decreases with increasing severity 42,45 , or CD-sens which is the inverse of EC 50 multiplied by 100 and can be calculated based on the slope of the dose-response curve 25,35 . CD-sens increases with the severity of allergic reactions 35 .…”
Section: Reactivity and Sensitivity Are Distinct Measures Of Basophilmentioning
confidence: 90%
“…One cause of non-responsiveness is a low level of Syk phosphatase [21][22][23] , possibly in combination with elevated amounts of CD45 13 . The non-responder phase is transient; a patient may revert to a responsive state within months 24,25 . The nonresponder state has also been reversed experimentally in vitro by culturing basophils in the presence of IL-3 26 .…”
Section: The Importance Of Non-ige and Ige-mediated Controls And The mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this procedure is contraindicated in patients with past severe food responses because it can cause allergic reactions of unpredictable severity. Basophil activation test (BAT) is a functional test useful for the diagnosis of pollen and food allergy and can be used to evaluate the possibility of more severe allergic reactions in patients with OAS [12,13]. Actually, BAT is reported to be quite specific and able to estimate the threshold of allergic reactions, as well as to discriminate between sensitized and symptomatic patients.…”
Section: Current Diagnostic Approachesmentioning
confidence: 99%
“…Clinically relevant hymenoptera allergy in patients with double sensitization to honeybee and vespid venoms was best diagnosed using BAT, thereby reducing the need for double venom immunotherapies 48 . A post hoc analysis including 3 peanut allergy cohorts concluded that BAT performs best to predict disease severity and the threshold of consumable peanut during oral food challenge (OFC) 49 . Interestingly, a study of 70 SLIT patients showed discrepancies between the use of whole peanut extract or Ara h 2 in BAT to predict the eliciting dose in double‐blinded OFC 50 .…”
Section: Diagnostic Approachesmentioning
confidence: 99%